Adaptation to university studies affects on functional state of freshmen - Marina Avdeeva (Universidade Estadual de Maringá, 2022)
According to different researches, 30% of university graduates have a low level of health, and studying at university is one of the factors of its deterioration, besides the first year is considered critical. The purpose of research is to study the dynamics of physical development, physical fitness and functional state of young men during the first year of university studies. For the survey we used standard measurements and index calculations for 11 indicators of physical development, 9 indicators of physical fitness and 15 indicators of functional status. We calculated the arithmetic mean (M), the standard error of the mean (m), then evaluated differences by the Student criterion (t) for independent samples and considered them as reliable atр < 0.05. It is shown that during the first year of studies, young men have an increase in the Erismann index, the corpulence (Rohrer's) index, the body mass index and a decrease in the Pignet index. There is also an increase in the coefficient of endurance, adaptive capacity and diastolic pressure, while vital capacity of the lungs, the vital index, time of hanging on the bar and the speed of running 1000 m decrease. The dynamics of physical development is expressed in a change in mass-growth indices and indicates an increase in body weight. The dynamics of physical fitness is expressed in a decrease of the time of hanging on the bar and the speed of running 1000 m. The dynamics of the functional state is expressed in a decrease of vital capacity of the lungs, vital index, increase in the coefficient of endurance, adaptive capacity and diastolic blood pressure.